STRUKTUR DAN DISTRIBUSI PENDAPATAN RUMAH TANGGA PETANI PADI SAWAH DI DESA MEREMBU KECAMATAN LABUAPI KABUPATEN LOMBOK BARAT - IDA AYU KETUT MARINI (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2022)
This study aims to determine the source and distribution of rice farmers' household income in Merembu Village, Labuapi District, West Lombok. This study uses a sample survey method to 35 respondents of farmer households as a sample in the research area. The technique of analyzing the structure of farmer household income uses descriptive statistical analysis through the accounting method (Rasahan, 1988). The analysis of the distribution of farmers' incomes uses three approaches, namely the Gini Analysis (Ratio Gini Coeficient), the Lorenz Curve approach and the World Bank Criteria. The results showed that the average income of lowland rice farmers in Merembu Village, Labuapi District, West Lombok ranged from Rp. 2.025.000 – Rp. 5,872,500. The average level of income outside of farming ranges from Rp. 1,184,618 - Rp. 2,206,430, with various sources of income as Baruh tani with an average income of Rp. 1,184,619, as a construction worker of Rp. 1,600,518, as a sand transporter Rp. 1,252,370 and as a basket trader Rp. 2,206,430. Income distribution analysis from the Gini Coefficient (GC) approach was obtained at 0.198, this means that the distribution of household income of low-income rice farmers in Merembu Village is in the category of mild inequality, this is reinforced by the Lorenz curve approach and the World Bank Criteria approach where 40% of farmers have low incomes. receive 25.97% share of all existing revenues